2012
DOI: 10.1073/pnas.1207188109
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of Sost distal enhancer increases bone formation and bone mass

Abstract: The Wnt antagonist Sost has emerged as a key regulator of bone homeostasis through the modulation of Lrp4/5/6 Wnt coreceptors. In humans, lack of Sclerostin causes sclerosteosis and van Buchem (VB) disease, two generalized skeletal hyperostosis disorders that result from hyperactive Wnt signaling. Unlike sclerosteosis, VB patients lack SOST coding mutations but carry a homozygous 52 kb noncoding deletion that is essential for the transcriptional activation of SOST in bone. We recently identified a putative bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 37 publications
5
111
0
Order By: Relevance
“…We have previously shown that conditionally knocking out a transcription factor, Mef2C, of Sost in osteoblasts results in a high bone mass phenotype similar to Sost -/-mice [83], which we would also expect to observe in Sost coinko; Col1 cre+.…”
Section: Chapter 5: Conclusion and Future Directionsmentioning
confidence: 59%
See 4 more Smart Citations
“…We have previously shown that conditionally knocking out a transcription factor, Mef2C, of Sost in osteoblasts results in a high bone mass phenotype similar to Sost -/-mice [83], which we would also expect to observe in Sost coinko; Col1 cre+.…”
Section: Chapter 5: Conclusion and Future Directionsmentioning
confidence: 59%
“…3). Consistent with the human SOST null phenotype, the high bone mass phenotype is recapitulated in Sost knockout mice (Sost -/-) with 3-4 times more bone mineral density (BMD) [89]. In contrast, transgenic mice with elevated levels of human SOST develop osteopenia [81] and limb defects [90].…”
Section: Sost As a Wnt Antagonist And Sost Antibodymentioning
confidence: 85%
See 3 more Smart Citations